Odhneria odhneri Travassos, 1921 (Trematoda: Microphallidae) in Migrant Shorebirds from Patagonia, Argentina - Capasso, Sofía Carolina (2017)
The aim of this paper is to describe Odhneria odhneri in migratory shorebirds at Patagonian sites. A total of 48 Calidris fuscicollis, 44 Calidris bairdii, and 5 Charadrius falklandicus from several areas in Argentinean Patagonia were examined. Adult specimens of O. odhneri were obtained from the intestinal cecae of C. bairdii (P=6.8, MI=30.3), and C. falklandicus (P=20, MI=17.5). Morphological and morphometric characteristics agree with those of previous records. This is the southernmost record for the trematode O. odhneri, and the first host record for C. bairdii and Ch. falklandicus. We propose that C. bairdii may act as a dispersing agent for O. odhneri between the America’s southern and northern hemispheres. Apparently, gastropod mollusks, crustaceans and birds are maintaining the life cycle of this species in Patagonia. The host, C. bairdii, has the potential of passing viable eggs of O. odhneri into the environment during their northward migration and onto their nesting sites during the boreal summer. This discovery broadens our knowledge about the range of hosts and the potential ways of dispersal of parasites along the American coast and, represents a valuable contribution to the general knowledge of shorebird parasites in South America.